Analisis Keseimbangan Statis pada Siswa SDN 004 Samarinda Ilir - Sherly Diana Putri; Gyta Krisdiana Cahyaningrum; Naheria Naheria; Jance Jacob Sapulete; Didik Cahyono; Muhammad Sukron Fauzi; Nurjamal Nurjamal (Departement of Mathematics Education, 2024)
This study aims to analyze static balance in students of SDN 004 Samarinda Ilir. Static balance is the ability to maintain a stable body position while standing or standing still. This research uses quantitative methods with a descriptive approach. Determination of the subject of this study using saturated sampling method by involving all grade 2 students at SDN 004 Samarinda Ilir, namely 30 students. Measurement of static balance using the stork stand test. Based on the results of data analysis, it shows that the ability of static balance in grade 2 students of SDN 004 Samarinda Ilir has a good static balance, namely 70% with an average duration of 20 seconds and there are 30% of students who get a shorter duration with an average of 13 seconds so that it falls into the category of less. So it can be concluded that the ability of static balance in grade 2 students at SDN 004 Samarinda Ilir is in the good category.